Images of medieval sanctity
1 online resource.
Keywords: Assembled on the occasion of Gary Dickson's retirement from the University of Edinburgh following a distinguished career as an internationally acclaimed scholar of medieval social and religious history, this volume contains contributions by both established and newer scholars inspired by Dickson’s particular interests in medieval popular religion, including ‘religious enthusiasm’. Together, the essays comprise a comprehensive and rich investigation of the idea of sanctity and its many medieval manifestations across time (fifth through fifteenth centuries) and in different geographical locations (England, Scotland, France, Italy, the Low Countries). By approaching the theme of sanctity from multiple disciplinary perspectives, this highly original collection pushes forward current academic thinking about medieval hagiography, iconography, social history, women's studies, and architectural history.